PHYTOMEMATODES FAUNA AND ECOLOGY OF NORTH-EASTERN UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study is dedicated to the study of the fauna and ecology of phytomematodes in the territory of North-Eastern Uzbekistan. The study analyzed the species of phytomematodes, their ecological characteristics, and their impact on various agroecosystems. The data can be applied to preserve the biodiversity of phytomematodes and increase agricultural productivity.